Development and Validation of a Model to Evaluate the Water Resources of a Natural Protected Area as a Provider of Ecosystem Services in a Mountain Basin in Southern Chile - Fernández-Alberti, Sandra; Abarca-del-Río, Rodrigo; Bornhardt, Cristian; Ávila, Andres (Frontiers in Earth Science, 2021)
The objective of this work is to validate a model to characterize and evaluate the water resources (supply and downstream demands) of the hydrological basins associated with the Conguillío National Park, located in the Andes Mountains in central-southern Chile (38°14'- 38°54'S). This area is part of the Chilean biodiversity hotspot, of the first geopark in Chile, and constitutes the core of the Araucaria biosphere reserve, which provides multiple ecosystem services. To describe the behavior of the water resources in the four main river sub-basins originating in the park, the Water Evaluation and Planning System (WEAP) software was used, which was calibrated and validated with local hydrological data from 2000 to 2015. The WEAP System allows to quantify parameters involved in the hydrological cycle and water consumption of the different user sectors, and their interrelationships, to establish the water balance of the basins. Water is supplied by rain and snow, which occurs from June to December upstream in the Andes, and feeds the rivers Cautín, Allipén, Quepe and Lonquimay, which maximum flows occur between June and September, and minimum flows between January and April. The evolution of the water demand during the year was determined for each sub-basin for the following user sectors: human consumption, agriculture, livestock, industry, electricity production, aquaculture and other uses. As expected, the main water consuming sector is agriculture, with an average of 79.4 Mm3/yr. Considering that mountain ecosystems are areas of high productivity value, but are very fragile and vulnerable to anthropic and climatic effects, the use of the obtained data and the calibrated/validated model describing and characterizing these resources, will allow future studies under different socio-economic and climate change scenarios, to assess the importance of mountain basin ecosystem services, providing an example for equivalent studies throughout South America.